Βιβλιοκρισία:G. HATZELIS, Byzantine military manuals as literary works and practical handbooks. The case of the tenth-century “Sylloge Tacticorum”, Routledge, London and New York 2019 - ΣΥΓΚΕΛΛΟΥ Ευστρατία (Byzantina Symmeikta, 2022)
Βιβλιοκρισία:G. Hatzelis, Byzantine military manuals as literary works and practical handbooks. The case of the tenth-century “Sylloge Tacticorum”, Routledge, London and New York 2019